BEHAVIOR TECHNIQUES TO REDUCE LAZY IN READING CASE STUDY ARTICLES OF PGRI BANYUWANGI UNIVERSITY STUDENTS - Riva Setyo Wati; Nurzaki Alhafiz; Agus Mursidi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
It is very important that students' interest in reading influences their learning outcomes, because a high interest in reading allows a person to understand the basics of science perfectly. The aim of this research is to what extent students increase their willingness to read to understand articles at PGRI Banyuwangi University in order to get the expected results from the research. The method used is descriptive qualitative. Data was obtained from active students in the Guidance and Counseling study program at PGRI Banyuwangi University who attended lectures from the 2nd and 4th semesters of the 2022 and 2023 classes. Qualitative research collected data by observation and interviews. The PGRI Banyuwangi University Guidance and Counseling Study Program class of 2022 and 2023 still do not understand how to read articles well and also as a requirement to support completing lecture assignments. With this, we still don't understand what is being done and what the student understands. Reading more articles is searched on the Google Scholar site than on other websites. The results show that to avoid laziness in reading, students must first understand how they learn and change their behavior to create a personalized learning plan. Stimulus given by lecturers to students who want to read articles for lectures and other assignments, so that they can gain knowledge about the articles they read while increasing their understanding of both the material and its content.